Profile Of SGPT (Serum Glutamic Pyruvic Transaminase) Levels In Active Smokers Aged 20-60 Years - Sholihatil Hidayati; Ahdiah Imroatul M; Dimas Taufiqur Rohman Sudarwo (LPPM Universitas dr. Soebandi, 2024)
Background: Cigarettes are one of the main risk factors for several chronic diseases that can result in death. This shows that cigarettes are a big problem for public health. Purpose: to determine the SGPT (Serum Glutamic Pyruvic Transaminase) level profile in active smokers aged 20-60 years Methods: This research is quantitative. The population in this study is active smoking patients at the Grand Raya Husada Clinic, Pandanarum Village, Lumajang Regency, which totals 60 active smoking patients. The data analysis technique used in this study is descriptive. Results: The results of laboratory examinations showed that serum SGPT (Serum Glutamic Pyruvic Transaminase) levels in 60 respondents showed that 55 respondents (91.67%) had normal SGPT levels. As many as 5 respondents (8.33%) showed high or abnormal SGPT levels. Conclusions: Normal SGPT levels in smokers aged 20-60 years were 91.67%, and high or abnormal SGPT levels were 8.33%.